(untitled) (International Journal of Advanced Research in Computer Science, 2017)
The Cloud computing is ever-growing field in the present scenario. With the build up of knowledge and also the advancement of technology, a huge quantity of knowledge is generated every day. Storage, accessibility and security of the data type major issues rise within the field of cloud computing. The present paper focuses on homomorphic encryption that is basically used for security of knowledge within the cloud. Homomorphic encryption is outlined because the technique of encryption within which specific operations may be administered on the encrypted data information. The data is kept on a remote server. The task here is working on the encrypted data information. There are two forms of homomorphic data encryption i.e., fully homomorphic encryption and partially homomorphic encryption. Fully homomorphic encryption permit impulsive computation on the ciphertext in a ring whereas the partly homomorphic encryption is that the one within which addition or multiplication operations may be administered on the conventional ciphertext. The homomorphic encryption plays a significant role in cloud computing because the encrypted information of corporations is keep in a very public cloud, therefore taking advantage of the cloud provider’s services. The various algorithms and ways of fully homomorphic encryption that have been projected are mentioned in this paper. Keywords: Cloud computing, Fully Homomorphic Encryption, Homomorphic encryption, Harmonic decryption, Security.